2019
DOI: 10.1242/jcs.230581
|View full text |Cite
|
Sign up to set email alerts
|

BOH1 cooperates with Polo-like kinase to regulate flagellum inheritance and cytokinesis initiation in Trypanosoma brucei

Abstract: Trypanosoma brucei possesses a motile flagellum that determines cell morphology and the cell division plane. Inheritance of the newly assembled flagellum during the cell cycle is controlled by the Polo-like kinase homolog TbPLK, which also regulates cytokinesis initiation. How TbPLK is targeted to its subcellular locations remains poorly understood. Here we report the trypanosome-specific protein BOH1 that cooperates with TbPLK to regulate flagellum inheritance and cytokinesis initiation in the procyclic form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 46 publications
(90 reference statements)
0
23
0
Order By: Relevance
“…The first evidence to demonstrate the involvement of the hook complex in flagellum inheritance was obtained from the functional characterization of a hook complex-localizing protein named TbLRRP1, which showed that knockdown of TbLRRP1 abolished FAZ assembly and caused flagellum detachment (8). Further evidence to support this notion came from the study of BOH1, which localizes to the hooked part of the hook complex and maintains hook complex morphology to control flagellum inheritance (22). In the current work, we identified BOH2, which co-localizes with BOH1 to the hooked part of the hook complex, and demonstrated its essential role in flagellum inheritance, thus providing additional evidence for the involvement of the hook complex in flagellum inheritance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first evidence to demonstrate the involvement of the hook complex in flagellum inheritance was obtained from the functional characterization of a hook complex-localizing protein named TbLRRP1, which showed that knockdown of TbLRRP1 abolished FAZ assembly and caused flagellum detachment (8). Further evidence to support this notion came from the study of BOH1, which localizes to the hooked part of the hook complex and maintains hook complex morphology to control flagellum inheritance (22). In the current work, we identified BOH2, which co-localizes with BOH1 to the hooked part of the hook complex, and demonstrated its essential role in flagellum inheritance, thus providing additional evidence for the involvement of the hook complex in flagellum inheritance.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is supported by the distinct defects on the hook complex and the centrin arm exerted by the knockdowns of BOH1 and BOH2. Depletion of BOH1 distorted the overall morphology of the hook complex and impaired the elongation of the centrin arm (22), whereas RNAi of BOH2 disrupted the integrity of the hook complex and inhibited the formation of the centrin arm (Figs. 4 and 5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 and 3) was functionally enriched for GO terms such as DNA replication and chromosome organization, and KEGG pathway term homologous recombination indicating that its genes are involved in the progression of cell cycle (Additional le 11: Figure S5 and Table 1). Additionally, the red module has some genes involved in cytokinesis such as BOH1 (Tb927.10.12720), that cooperates with TbPLK to initiate cytokinesis and agellum inheritance [42], and Cytokinesis Initiation Factor 2 (CIF2) (Tb927.9.14290) which is involved in initiation of cytokinesis [43] (Additional le 6). Other genes assigned to this module were in concordance with the enriched functions.…”
Section: Discussionmentioning
confidence: 99%